Optimal high-throughput screening : practical experimental design and data analysis for genome-scale RNAi research - Zhang, Xiaohua Douglas (Cambridge University Press, 2011)
"This book focuses on commonly used and recently developed methods for designing and analyzing high-throughput screening experiments from a statistically sound basis"--Provided by publisher.